2019
DOI: 10.1186/s13075-019-2092-7
|View full text |Cite
|
Sign up to set email alerts
|

Rule-based and machine learning algorithms identify patients with systemic sclerosis accurately in the electronic health record

Abstract: BackgroundSystemic sclerosis (SSc) is a rare disease with studies limited by small sample sizes. Electronic health records (EHRs) represent a powerful tool to study patients with rare diseases such as SSc, but validated methods are needed. We developed and validated EHR-based algorithms that incorporate billing codes and clinical data to identify SSc patients in the EHR.MethodsWe used a de-identified EHR with over 3 million subjects and identified 1899 potential SSc subjects with at least 1 count of the SSc IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 13 publications
2
33
0
Order By: Relevance
“…To accurately capture rare diagnoses, other more structured parts of the EHR may be useful such as laboratory results. A well-performing example is a simple classification algorithm for the identification of patients with systemic sclerosis in the EHR by using positive antinuclear antibody titer thresholds 26 .…”
Section: Discussionmentioning
confidence: 99%
“…To accurately capture rare diagnoses, other more structured parts of the EHR may be useful such as laboratory results. A well-performing example is a simple classification algorithm for the identification of patients with systemic sclerosis in the EHR by using positive antinuclear antibody titer thresholds 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Using EMR data, ML has been used to explore electronic health record-phenotyping [86][87][88], to conduct population-based analysis [89], and to evaluate patient experiences [90]. NLP has been used to analyze EMR with the aim to identify atopic dermatitis.…”
Section: Facilitating Large-scale Epidemiology Researchmentioning
confidence: 99%
“…ML methods can also be used to phenotype rare diseases, such as systemic sclerosis in EMR data. One study found that the highest performing ML methods to phenotype systemic sclerosis incorporated clinical data with billing codes [88]. Another study used NLP to develop the first population-based estimates of melanocytic lesions from EMR pathology reports [89].…”
Section: Facilitating Large-scale Epidemiology Researchmentioning
confidence: 99%
“…Manual review of these data is time consuming and laborious, hampering the usability of the data. Advancements in Natural Language Processing and Machine Learning (ML) methods have created great potential for processing format-free text data such as present in EHRs [1,2]. These EHR entries contain the prosaic conclusion of the treating physician, ranging from elaborate discussion of lab results to listed differential diagnoses.…”
Section: Introductionmentioning
confidence: 99%